A novel case of chronic mucocutaneous candidiasis: Overlap between autoimmune polyendocrinopathy, candidiasis, ectodermal dystrophy syndrome and hyper IgE syndrome - Bauyelal Mahto; Payel Kundu; Aniruddha Ghosh; Sandipan Dhar (Wolters Kluwer Medknow Publications, 2018)
Chronic mucocutaneous candidiasis (CMC) is a clinical entity where extensive fungal infection of skin, hair, nail, and mucosa with Candida sp. is seen. It has got association with several immunological and endocrinal dysfunctions. We report a case of a 14-year-old boy who presented with peculiar facies, gross failure to thrive, fungal granulomatous lesions with scaring alopecia, oropharyngeal candidiasis, ectodermal dystrophy, grade 3 clubbing of all four limbs, interstitial keratitis with leukoma due to recurrent corneal ulcerations, and persistent deciduous teeth. A diagnosis of CMC was made and evaluation of immunological pathways revealed a high titer of immunoglobulin E. CMC with overlapping features of autoimmune polyendocrinopathy candidiasis ectodermal dystrophy syndrome and hyper IgE syndrome is extremely rare in literature. Timely diagnosis of an underlying etiology and proper treatment of a case of CMC may provide a better quality of life of the patient.